Catalyst for ammonia decomposition and production method therefor, and ammonia decomposition method
Patent Information
- Application Number
- JP2023129454
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-21
AI Technical Summary
【0016】 本発明に係るアンモニア分解用触媒は、アンモニアを窒素と水素を含む混合改質ガスへ分解する触媒であり、600℃以下の温度帯でも高いアンモニア分解用触媒活性がある。さらに、複数回繰り返して使用することが可能なアンモニア分解用触媒である。
Smart Images

Figure 2025025021000001 
Figure 2025025021000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an ammonia decomposition catalyst for decomposing ammonia, a method for producing the same, and a method for producing nitrogen and hydrogen using the ammonia decomposition catalyst. [Background technology]
[0002] Hydrogen, which is expected to be a new energy source, can also be obtained by decomposing ammonia. However, currently, catalysts carrying precious metal elements are generally used to produce hydrogen from ammonia gas, making the system very expensive. In particular, the price of the catalyst accounts for the majority of the cost of the entire hydrogen production system.
[0003] In other words, the spread of the system will be promoted by realizing lower prices as well as further improving the performance of catalysts. Therefore, there is a strong demand to switch from catalysts that use large amounts of precious metal elements to catalysts that use less expensive elements in as small amounts as possible.
[0004] Furthermore, it is desirable for the catalyst to be reusable multiple times, and therefore the catalyst is required to have sufficient strength so that sufficient cracking catalytic activity can be obtained even after repeated use. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-224555 A Summary of the Invention [Problem to be solved by the invention]
[0006] The ammonia decomposition catalyst disclosed in the above-mentioned Patent Document 1 contains nickel in a large amount of 55 to 95 mass % based on the total amount of the catalyst, so that the metallic nickel is sintered and the nickel particle size becomes large, and therefore sufficient ammonia decomposition properties cannot be obtained. [Means for solving the problem]
[0007] The above technical problems can be solved by the present invention as follows.
[0008] That is, the present invention provides an ammonia decomposition catalyst that contains at least magnesium, aluminum, and nickel, the magnesium and aluminum being in the form of a composite oxide, the nickel being metallic nickel, and containing 10 to 50 wt% magnesium, 5 to 35 wt% aluminum, and 1 to 30 wt% nickel (Invention 1).
[0009] The present invention also relates to the catalyst for decomposing ammonia according to Invention 1, wherein the average particle size of the metallic nickel in the catalyst is 1 to 50 nm. (Invention 2)
[0010] The present invention also relates to the catalyst for decomposing ammonia according to the first aspect, 2 / g. (Invention 3)
[0011] The present invention also relates to the catalyst for decomposing ammonia according to Invention 1, which contains one or more metals selected from gold, silver, platinum, palladium, ruthenium, cobalt, iron, rhodium, iridium, rhenium, copper, manganese, chromium, vanadium, and titanium, each having an average particle size of 50 nm or less. (Invention 4)
[0012] The present invention also provides the catalyst for decomposing ammonia according to the first aspect, wherein the average crushing strength of the catalyst is 3 kgf / cm 2 The above is an ammonia decomposition catalyst. (Invention 5)
[0013] The present invention also provides a method for decomposing ammonia, which uses the ammonia decomposition catalyst according to Invention 1. (Invention 6)
[0014] A method for producing a mixed reformed gas containing hydrogen and nitrogen by reacting ammonia in the presence of the ammonia decomposition catalyst described in Invention 1. (Invention 7)
[0015] The present invention also relates to a method for producing an ammonia decomposition catalyst according to Invention 1, which comprises producing hydrotalcite particles containing constituent elements as a precursor by a coprecipitation reaction, forming a molded body, calcining the molded body to form a porous catalyst body, and then reducing the molded body by heating. (Invention 8) Effect of the Invention
[0016] The ammonia decomposition catalyst according to the present invention is a catalyst that decomposes ammonia into a mixed reformed gas containing nitrogen and hydrogen, and has high catalytic activity for decomposing ammonia even in a temperature range of 600° C. or less. Furthermore, the ammonia decomposition catalyst can be used repeatedly multiple times. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The configuration of the present invention will be described in detail as follows.
[0018] First, the ammonia decomposition catalyst according to the present invention will be described.
[0019] The catalyst for decomposing ammonia according to the present invention is characterized in that it contains at least magnesium, aluminum and nickel, the magnesium and aluminum being a composite oxide, the nickel being metallic nickel, and containing 10 to 50 wt% magnesium, 5 to 35 wt% aluminum and 1 to 30 wt% nickel. In addition to magnesium, aluminum and nickel, elements such as sodium, silicon and zinc may be contained, but are not limited thereto. If calcium is contained, there is a risk that the catalyst will not have the desired strength, so it is preferable to configure the catalyst without containing calcium.
[0020] The magnesium content of the ammonia decomposition catalyst according to the present invention is 10-50wt% relative to the catalyst. If the magnesium content is less than 10wt%, the BET specific surface area of the catalyst becomes small and the catalyst becomes less porous, which may reduce the probability of contact with gas, and furthermore, the resistance to sulfur poisoning is also reduced. If the magnesium content exceeds 50wt%, the mechanical strength is reduced. The magnesium content is preferably 15-45wt%, more preferably 20-40wt%.
[0021] The aluminum content of the ammonia decomposition catalyst according to the present invention is 5-35 wt% based on the catalyst. If the aluminum content is less than 5 wt%, the mechanical strength is reduced. If the aluminum content exceeds 35 wt%, the BET specific surface area is reduced and the catalyst is no longer porous, which may reduce the probability of contact with gas. The aluminum content is more preferably 6-30 wt%, and even more preferably 7-25 wt%.
[0022] The magnesium and aluminum in the ammonia decomposition catalyst according to the present invention may be contained in the catalyst in the form of a composite oxide. In the ammonia decomposition catalyst according to the present invention, only the nickel component is precipitated as fine particle metallic nickel from an oxide containing magnesium, aluminum and nickel, such as a periclase type structure or a spinel type structure, by reduction heat treatment, and the oxide containing magnesium and aluminum is made to contain nickel metal on the surface and / or pore surface.
[0023] The nickel content of the ammonia decomposition catalyst according to the present invention is 1 to 30 wt% relative to the catalyst. If the nickel content is less than 1 wt%, sufficient catalytic activity may not be obtained, resulting in a decrease in the ammonia gas decomposition rate. If the nickel content exceeds 30 wt%, the particle size of the metallic nickel fine particles exceeds 50 nm and grows large, resulting in a decrease in the ammonia gas decomposition rate and a high catalytic activity temperature. In consideration of economic efficiency, it is preferable to have a small amount of nickel within the range of the content that provides sufficient catalytic activity. The nickel content is more preferably 5 to 25 wt%, and even more preferably 10 to 20 wt%.
[0024] The nickel content (Ni / (Mg+Al+Ni)) of the ammonia decomposition catalyst according to the present invention is preferably 0.05 to 0.55 (molar ratio) relative to the total amount of Mg, Al and Ni.
[0025] The ratio of magnesium to aluminum in the ammonia decomposition catalyst according to the present invention is not particularly limited, but it is preferable that there is more magnesium relative to aluminum, and the molar ratio of magnesium to aluminum is more preferably Mg:Al=5:1 to 1:1. If the magnesium exceeds the above range, it becomes difficult to easily obtain a molded body having sufficient strength, and if it is below the above range, it becomes difficult to obtain the characteristics of a porous carrier.
[0026] The average particle size of the metallic nickel contained in the ammonia decomposition catalyst according to the present invention is preferably 1 to 50 nm. Outside this range, there is a risk that sufficient catalytic activity will not be obtained. The average particle size of the metallic nickel contained in the catalyst is more preferably 5 to 40 nm, and further preferably 8 to 30 nm.
[0027] The catalyst for decomposing ammonia according to the present invention is one in which metallic nickel is present in a composite oxide containing magnesium and aluminum. The metallic nickel in the catalyst for decomposing ammonia according to the present invention is preferably present in the vicinity of the surface of the particles constituting the catalyst. The catalyst for decomposing ammonia according to the present invention is preferably used in the form of a granulated molded body, and metallic nickel may be present in the vicinity of the surface of the molded body. The catalyst for decomposing ammonia according to the present invention contains metallic nickel in the form of very fine particles. Therefore, the area in which metallic nickel, which is an active metal species, comes into contact with ammonia is increased, and ammonia can be decomposed into a gas containing nitrogen and hydrogen, and the catalyst has excellent catalytic activity.
[0028] The BET specific surface area of the ammonia decomposition catalyst according to the present invention is 5 to 100 m 2 / g is preferred. BET specific surface area is 5m 2 If the BET specific surface area is less than 100 m / g, the pore size becomes too large and there is a risk that the active metal species cannot be sufficiently dispersed and supported. 2 If the thickness exceeds 15 to 80 mm / g, sufficient strength may not be obtained. 2 / g, more preferably 20 to 60m 2 / g.
[0029] The ammonia decomposition catalyst according to the present invention may support other metals in addition to nickel. By supporting other metals as active metal species on the ammonia decomposition catalyst according to the present invention, higher decomposition catalytic activity can be expected.
[0030] The supported metal in the present invention is not particularly limited, and may be a noble metal element or a base metal element. Examples of supported metals include gold, silver, platinum, palladium, ruthenium, cobalt, rhodium, iridium, rhenium, copper, manganese, chromium, vanadium, titanium, and iron, and may be used alone or in combination of two or more. The supported metal may be simultaneously contained in the porous catalyst body when it is produced, or may be supported after the porous catalyst body is produced, and is not particularly limited. The supporting method is also not particularly limited, and may be a commonly used method such as a spray drying method or an impregnation method.
[0031] The average particle size of the supported metal in the present invention is preferably 50 nm or less, more preferably 40 nm or less, and even more preferably 30 nm or less. If the average particle size of the supported metal exceeds 50 nm, there is a risk that the supporting effect cannot be obtained. The lower limit of the average particle size of the supported metal is not particularly limited, but is preferably about 0.5 nm. By including the supported metal, the catalytic activity in a relatively low temperature range of 600 ° C or less can be further improved.
[0032] The supported metal in the present invention is preferably contained since it becomes an active metal species, and the preferred content is about 0.01 to 10 wt% of the catalyst. If it is less than 0.01 wt%, sufficient ammonia decomposition properties cannot be obtained, and if it exceeds 10 wt%, the cost increases, which is not industrially preferred.
[0033] The catalyst for ammonia decomposition according to the present invention can be made into a molded body. The shape and size are not particularly limited, and may be, for example, various shapes such as spherical, cylindrical, tubular, pellet, or the like, or may be in the form of a coating on a honeycomb body. In general, the size of a catalyst having a spherical, cylindrical, or tubular shape is about 0.1 to 30 mm, and a spherical shape is preferable from the viewpoint of packing into a column, etc. The molded body of the catalyst for ammonia decomposition may be adjusted in strength or pore distribution density by adding various binders such as organic or inorganic substances.
[0034] The average crushing strength of the ammonia decomposition catalyst according to the present invention is 3 kgf / cm 2More than 3kgf / cm is preferable. 2 If it is less than this, it may expand and shrink due to heating during repeated use, or be crushed by external stress, resulting in a risk of not being able to obtain the desired catalytic activity, or of cracking, destruction, or powdering occurring when used at high temperatures. The average crushing strength is 4 to 50 kgf / cm 2 More preferably, it is 5 to 40 kgf / cm 2 It is.
[0035] The pore volume of the ammonia decomposition catalyst according to the present invention is 0.01 to 0.50 cm 3 / g is preferred. 3 If the surface area is less than 0.50 cm3 / g, nickel and other supported metals may not be sufficiently dispersed and supported. 3 If the pore volume exceeds 0.02 to 0.45 cm3 / g, the mechanical strength may be weakened. 3 / g, and more preferably 0.05 to 0.40 cm 3 / g.
[0036] The ammonia decomposition catalyst according to the present invention has a high average crushing strength, and therefore can maintain the same ammonia gas decomposition rate as the first time it is used repeatedly, i.e., has excellent cycle characteristics. The ammonia decomposition catalyst according to the present invention not only exhibits a high ammonia gas decomposition rate in a relatively low temperature range of 600°C or less, but can also be used repeatedly, making it environmentally and economically excellent. In addition, the ammonia decomposition catalyst according to the present invention has excellent strength, so there is little risk of the shape or decomposition characteristics changing even when it is packed into a column or the like for use, making it industrially preferable.
[0037] Next, a method for producing the ammonia decomposition catalyst according to the present invention will be described.
[0038] The method for producing the ammonia decomposition catalyst according to the present invention is not particularly limited, but it is preferable to produce hydrotalcite particles containing the constituent elements by a coprecipitation reaction as a precursor, prepare a molded body, heat and sinter it to form a porous catalyst body, and then heat and reduce it to produce the catalyst.
[0039] The hydrotalcite particles containing magnesium, aluminum and nickel in the present invention are preferably obtained by mixing an anion-containing alkaline aqueous solution with an aqueous solution of a magnesium raw material, an aluminum raw material and a nickel raw material to obtain a mixed solution having a pH value in the range of 7.0 to 13.0, aging the mixed solution in the temperature range of 50 to 300°C, and then filtering and separating the resultant mixture, followed by drying.
[0040] The maturation time in the first stage is not particularly limited, but is preferably 1 to 80 hours, more preferably 3 to 24 hours, and further preferably 5 to 18 hours. A growth reaction for more than 80 hours is not industrially feasible.
[0041] The magnesium, aluminum, and nickel raw materials are not particularly limited as long as they are water-soluble, such as nitrates.
[0042] As the magnesium raw material, magnesium oxide, magnesium hydroxide, magnesium oxalate, magnesium sulfate, magnesium sulfite, magnesium nitrate, magnesium chloride, magnesium citrate, basic magnesium carbonate, magnesium benzoate, etc. can be used.
[0043] As the aluminum source, aluminum oxide, aluminum hydroxide, aluminum acetate, aluminum chloride, aluminum nitrate, aluminum oxalate, basic ammonium aluminum, etc. can be used.
[0044] As the nickel salt raw material, nickel oxide, nickel hydroxide, nickel sulfate, nickel carbonate, nickel nitrate, nickel chloride, nickel benzoate, basic nickel carbonate, nickel formate, nickel citrate, diammonium nickel sulfate, etc. can be used.
[0045] In addition, various methods can be used as a method for supporting nickel contained in the catalyst for ammonia decomposition according to the present invention. For example, there is a method in which nickel is supported on a porous catalyst body containing magnesium and aluminum by a normal precipitation method, a heat impregnation method, a room temperature impregnation method, a vacuum impregnation method, an equilibrium adsorption method, an evaporation to dryness method, a competitive adsorption method, an ion exchange method, a spray method, a coating method, or the like, or a method in which nickel is dissolved as a spinel crystal structure compound containing magnesium and aluminum, and metallic nickel is precipitated on a spinel support containing magnesium and aluminum by heat treatment.
[0046] Also, a method is known in which hydrotalcite particles are calcined to obtain composite oxide particles, and then the composite oxide particles are hydrated with an anion-containing aqueous solution to obtain layered double hydroxide particles. In the present invention, nickel may be contained by the following production method. The nickel-containing hydrotalcite particles may be calcined by heating as necessary, and then reduced by heating.
[0047] That is, the porous catalyst body in the present invention may support active metal species by a method in which a nickel-containing hydrotalcite phase is regenerated in the vicinity of the surface of the ammonia decomposition catalyst or molded body by impregnation with a solution containing nickel.
[0048] The average plate surface diameter of the hydrotalcite particles containing magnesium, aluminum and nickel in the present invention is preferably 0.05 to 0.4 μm. If the average plate surface diameter is less than 0.05 μm, filtration and washing with water become difficult, making industrial production difficult, and if it exceeds 0.4 μm, it is difficult to prepare a porous catalyst body.
[0049] The crystallite size D006 of the hydrotalcite particles in the present invention is preferably 0.001 to 0.08 μm. If the crystallite size D006 is less than 0.001 μm, the viscosity of the aqueous suspension is very high, making industrial production difficult, and if it exceeds 0.08 μm, it is difficult to prepare a porous catalyst body. The more preferred range of the crystallite size D006 is 0.002 to 0.07 μm.
[0050] The BET specific surface area of the hydrotalcite particles containing magnesium, aluminum and nickel in the present invention is 3.0 to 300 m 2 / g is preferable. 2 If the average particle size is less than 300 m / g, it is difficult to prepare a porous catalyst body. 2 If the specific surface area exceeds 5.0 to 250 m / g, the viscosity of the aqueous suspension will be very high, and filtration and washing with water will be difficult, making industrial production difficult. 2 / g.
[0051] In the present invention, the ratio of magnesium to aluminum in the hydrotalcite containing magnesium and aluminum is not particularly limited, but the molar ratio of magnesium to aluminum is preferably Mg:Al=4:1 to 1:1.
[0052] The secondary agglomerate particle diameter of the hydrotalcite particles in the present invention is preferably 0.1 to 200 μm. If the secondary agglomerate particle diameter of the hydrotalcite particles is less than 0.1 μm, pulverization becomes difficult, making industrial production difficult. If it exceeds 200 μm, it is difficult to prepare a molded body. The secondary agglomerate particle diameter of the hydrotalcite particles is more preferably in the range of 0.2 to 100 μm.
[0053] The pulverization process can be carried out using a general pulverizing device (such as an atomizer, a yariya, or a Henschel mixer).
[0054] The molded body in the present invention is preferably prepared by adding a molding aid, a binder, and water and alcohol as a dispersion medium or a combustible substance as necessary to the hydrotalcite particles containing at least magnesium, aluminum, and nickel, kneading the mixture into a clay-like mixture in a kneading machine (screw kneader, etc.), and then molding the mixture. Methods for molding that can be used include compression molding, press molding, tablet molding, etc.
[0055] The molded body in the present invention is not particularly limited, and may have any shape that is commonly used for catalysts. Examples of the shape of the molded body include a sphere, a cylinder, a hollow cylinder, and a pellet.
[0056] When the molded article in the present invention is spherical, the size of the molded article is preferably 0.5 to 30 mmφ, more preferably 1 to 10 mmφ, and further preferably 2 to 8 mmφ.
[0057] The molding aid in the present invention may be a composition containing fatty acid, cellulose, polyvinyl alcohol, starch, methyl cellulose, maltose, carboxymethyl cellulose, etc., and two or more of them may be used in combination. The molding aid is burned and eliminated by the firing treatment and does not remain in the porous catalyst body. The amount of the molding aid to be added is preferably, for example, 1 to 50 parts by weight based on 100 parts by weight of the hydrotalcite particles containing magnesium, aluminum, and nickel.
[0058] The binder in the present invention may be a composition containing non-rehydratable alumina, α-alumina, aluminum salt, silica, clay, talc, bentonite, zeolite, cordierite, titania alkali metal salt, alkaline earth metal salt, rare earth metal salt, zirconia, mullite, sepiolite, montmorillonite, halloysite, saporite, stevensite, hectorite, silica alumina, etc., and two or more of them may be used in combination. When a salt other than an oxide is added, it is important that the salt is decomposed to an oxide by firing. The amount of addition is preferably, for example, 1 to 50 parts by weight based on 100 parts by weight of hydrotalcite particles containing magnesium and aluminum.
[0059] Examples of the alcohols that can be used in the present invention include monohydric alcohols such as ethanol and propanol, glycols such as ethylene glycol, propylene glycol, butanediol and polyethylene glycol, and polyhydric alcohols such as glycerin, and two or more of these may be used in combination. The amount of the alcohol added is preferably, for example, 50 to 150 parts by weight per 100 parts by weight of the hydrotalcite particles containing magnesium and aluminum.
[0060] In addition, as the combustible material in the present invention, wood chips, cork grains, coal powder, activated carbon, crystalline cellulose powder, starch, sucrose, gluconic acid, polyethylene glycol, polyvinyl alcohol, polyacrylamide, polyethylene, polystyrene, etc., and mixtures thereof may be added. The more the amount of the combustible material added, the larger the pore volume becomes, but adding too much of the material causes a decrease in strength, so the amount added can be adjusted taking the strength into consideration.
[0061] When a honeycomb shape is to be formed, a method may be freely selected according to need.
[0062] The molded product molded by the above method can be dried by natural drying, hot air drying, vacuum drying, or the like.
[0063] Furthermore, the porous catalyst body of the present invention can be obtained by heat-treating the molded body. The heat treatment temperature is preferably 700°C to 1500°C. If the heat treatment temperature is less than 700°C, a long period of heat treatment is required to maintain the crushing strength, which is not industrially feasible. If the heat treatment temperature exceeds 1500°C, the pores of the porous catalyst body may be crushed. The heat treatment temperature is more preferably 800°C to 1400°C, and even more preferably 900°C to 1300°C.
[0064] The heat treatment time is preferably 1 to 72 hours. If the heat treatment time is less than 1 hour, the crushing strength decreases, and if it exceeds 72 hours, the pores of the porous catalyst body are crushed, and a long heat treatment is not industrially practical. The heat treatment time is more preferably 2 to 60 hours, and further preferably 3 to 50 hours.
[0065] The catalyst for ammonia decomposition according to the present invention is obtained by subjecting the porous catalyst body to a reduction treatment. The reduction temperature is preferably 700°C to 1000°C. If the reduction temperature is less than 700°C, nickel is not metallized, and the catalytic activity aimed at by the present invention may not be obtained. If the reduction temperature exceeds 1000°C, sintering of nickel proceeds, and the particle size of the metallic nickel fine particles increases, and the ammonia decomposition rate at low temperatures may decrease. The reduction temperature is more preferably 750 to 950°C. The atmosphere during reduction is not particularly limited as long as it is a reducing atmosphere such as a gas containing hydrogen. The reduction treatment time is not particularly limited, but is preferably 0.5 to 24 hours. If it exceeds 24 hours, no industrial merit is found. The reduction treatment time is more preferably 1 to 10 hours.
[0066] Next, a method for decomposing ammonia using the ammonia decomposition catalyst according to the present invention will be described.
[0067] The ammonia decomposition catalyst according to the present invention is capable of decomposing ammonia by contacting the ammonia, and can produce gases containing hydrogen, nitrogen, and the like.
[0068] The method for decomposing ammonia using the ammonia decomposition catalyst according to the present invention is not particularly limited as long as the method involves contacting ammonia with the ammonia decomposition catalyst according to the present invention in a temperature range (reaction temperature) in which the catalyst has catalytic activity.
[0069] The reaction temperature of the ammonia decomposition catalyst according to the present invention is preferably 300° C. to 800° C., more preferably 400° C. to 750° C., and even more preferably 500° C. to 700° C. If the reaction temperature is less than 300° C., there is a risk that a sufficient ammonia decomposition rate will not be obtained. If the reaction temperature exceeds 800° C., ammonia is completely decomposed, so there is little point in raising the reaction temperature to a high temperature, and it is a waste of energy.
[0070] The ammonia used in the present invention is not particularly limited, and may be synthetic ammonia or a mixture containing ammonia. The purity is also not particularly limited, and may be selected according to the purpose. The ammonia used in the present invention that is liquid at room temperature may be vaporized using a vaporizer before use.
[0071] The ammonia gas concentration in the ammonia gas decomposition method using the ammonia decomposition catalyst according to the present invention is not particularly limited, but is preferably 0.1% to 100%. If the ammonia gas concentration is less than 0.1%, there is a risk that sufficient hydrogen and nitrogen cannot be obtained.
[0072] The gas space velocity (GHSV) of the method for decomposing ammonia gas containing gas using the ammonia decomposition catalyst according to the present invention is 200 to 100,000 h -1 is preferred. GHSV is 200h -1 If the time is less than 100,000 hours, the amount of hydrogen and / or nitrogen gas obtained per unit time may be small. -1 If the time exceeds this limit, there is a risk that ammonia decomposition may not be sufficient. -1 is more preferable, and 500 to 50,000 h -1 is more preferred.
[0073] The present inventors presume that the reason why the ammonia decomposition catalyst according to the present invention is capable of decomposing ammonia gas is as follows.
[0074] The ammonia decomposition catalyst according to the present invention can exhibit high crushing strength by generating a spinel phase containing magnesium, aluminum and nickel through high-temperature calcination, and therefore can maintain high catalytic activity without the catalyst molded body bursting or pulverizing even when used multiple times, resulting in excellent cycle characteristics (reusability).
[0075] In addition, because it contains highly dispersed fine particles of metallic nickel, it is active at lower temperatures than conventional ammonia decomposition catalysts, which also leads to power savings.
[0076] Furthermore, since the ammonia decomposition catalyst according to the present invention contains a large amount of magnesium, it has excellent resistance to sulfur poisoning and has excellent catalytic activity in terms of durability as well.
[0077] The metallic nickel in the ammonia decomposition catalyst according to the present invention is in the form of very fine particles, particularly fine particles of 1 to 50 nm, and is present throughout the catalyst particles, in the vicinity of the surface of the catalyst particles, or in the vicinity of the surface of the catalyst molded body. This increases the area in which the metallic nickel, which is an active metal species, comes into contact with ammonia, and provides excellent catalytic activity even in a temperature range of 600°C or less.
[0078] The catalyst for ammonia decomposition according to the present invention is produced by calcining a precursor formed from hydrotalcite, which is a layered double hydroxide. The moisture in the hydrotalcite is dehydrated by high-temperature calcination, and the catalyst contains a large number of fine pores. Therefore, the specific surface area and pore volume are very large. Furthermore, pores are formed by removing moisture and carbonate ions between the layers of the hydrotalcite during calcination, and the pore diameter can be reduced. Therefore, the catalyst for ammonia decomposition according to the present invention can maintain a high specific surface area even when calcined at high temperatures, and can maintain a large BET specific surface area and pore volume, and can maintain catalytic activity for a long period of time.
[0079] The ammonia decomposition catalyst according to the present invention can support active metal species such as gold, silver, platinum, palladium, ruthenium, cobalt, rhodium, iridium, rhenium, copper, manganese, chromium, vanadium, and titanium, and can improve the catalytic activity and oxidation resistance. EXAMPLES
[0080] Examples of the present invention will be described below, but the present invention is not limited to these.
[0081] The crushing strength of the catalyst molded body was measured using a digital force gauge manufactured by IMADA in accordance with JIS Z8841 (granulated material - strength test method), and the average value was calculated from the measurements of 100 pieces to obtain the average crushing strength.
[0082] The pore volume was determined by the BJH method using a TriStar 3000 manufactured by Shimadzu Corporation.
[0083] The sizes of metallic nickel particles, ruthenium (Ru), and platinum (Pt) particles were measured from transmission electron microscope (JEM-F200, manufactured by JEOL Ltd.), and the average value of 360 or more primary particles was taken as the average particle diameter.
[0084] Identification of the hydrotalcite particles and evaluation of the morphology of Mg and Al in the ammonia decomposition catalyst were performed by X-ray diffraction measurement (X-ray diffractometer RINT-2500 (manufactured by Rigaku Corporation)). The X-ray diffraction measurement was performed using the X-ray diffractometer at a diffraction angle 2θ of 3 to 80°.
[0085] The contents of magnesium, aluminum and nickel in the ammonia decomposition catalyst were determined by dissolving the catalyst in acid and measuring the content by a plasma emission spectrometer SPS4000 (Seiko Denshi Kogyo Co., Ltd.).
[0086] The BET specific surface area was measured by the nitrogen BET method.
[0087] The ammonia gas concentration was evaluated using a Shimadzu gas chromatograph GC2014.
[0088] Example 1 MgSO 4 7H 2 O (261.99g) and Al 2 (SO 4 ) 3 8H 2 86.16 g of O was dissolved in water to make 1000 ml. 2 CO 3 (100.49 g) was dissolved in 1000 ml of the solution to prepare a total of 2000 ml of an alkaline mixed solution. The mixed solution of magnesium salt and aluminum salt was added to this alkaline mixed solution, and the mixture was aged at 95° C. for 8 hours to obtain an alkaline suspension. The pH of the reaction solution at this time was 12.8.
[0089] The alkaline suspension was then added with MgSO 4 7H 2 O (30.10 g) and NiSO 4 6H 2 O (60.01g) and Al 2 (SO 4 ) 3 8H 2 500 ml of a mixed solution of magnesium salt, nickel salt and aluminum salt containing O (120.20 g) was added, the pH of the reaction solution was adjusted to 11.4, and the solution was further aged at 120° C. for 4 hours to obtain hydrotalcite particles.
[0090] The obtained hydrotalcite particles (5400g) were mixed with boehmite (300g), PVA (3820g), water (300g) and propylene glycol (220g) and kneaded with a screw kneader. After kneading, the mixture was molded into a spherical shape with a diameter of 3mmφ, dried at 100°C, and then calcined in air at 800°C for 4 hours, and reduced at 700°C in an air stream containing hydrogen and argon gas for 1 hour to obtain an ammonia decomposition catalyst. It was confirmed that the obtained ammonia decomposition catalyst had a spinel structure, contained Mg and Al in the form of a composite oxide, and contained Ni in the form of a metal. The size of the obtained ammonia decomposition catalyst was a sphere with a diameter of 3mmφ. The Ni / (Mg+Al+Ni) in the obtained catalyst was 0.158 (molar ratio).
[0091] Table 1 shows the composition (Mg, Al, Ni) contained in the catalyst, the average Ni particle size, the BET specific surface area, the average crushing strength, and the pore volume.
[0092] The catalytic activity of the ammonia decomposition catalyst was evaluated as the ammonia gas decomposition rate. To evaluate the ammonia decomposition rate, a stainless steel reaction tube with a diameter of 10 mm was filled with 10 to 30 g of the ammonia decomposition catalyst to create a catalyst tube. Ammonia gas (concentration 100%, flow rate 500 ml / min) was fed as the raw gas to this catalyst tube (reactor) at atmospheric pressure, reaction temperature 400°C to 600°C, and space velocity 3000 h -1 After 10 minutes had elapsed and the catalyst temperature had stabilized, the ammonia gas concentrations at the inlet and outlet were evaluated and the ammonia gas decomposition rate was calculated.
[0093] The ammonia gas decomposition rate (%) was calculated from the following formula. Ammonia gas decomposition rate (%) = ((inlet ammonia gas concentration - outlet ammonia gas concentration) / inlet ammonia gas concentration) x 100
[0094] The catalyst tube that had undergone the reaction once was counted as one use, and the catalyst tube that had undergone the reaction was reused to evaluate the ammonia gas decomposition rate of the ammonia decomposition catalyst. This was repeated 3, 5, and 10 times to evaluate the ammonia gas decomposition rate, and the cycle characteristics were evaluated.
[0095] Table 2 shows the ammonia decomposition rates at reaction temperatures of 400°C, 500°C, and 600°C, and the ammonia decomposition rates when the reaction cycle was carried out up to 10 times.
[0096] <Example 2> Al 2 (SO 4 ) 3 8H 2 O (740.52 g) and NiSO 4 6H 2 15.34 g of 2H2O was dissolved in water to make 1500 ml. 2 CO 3 (12.60 g) was dissolved in 500 ml of the solution to prepare a total of 2000 ml of an alkaline mixed solution. The alkaline suspension obtained in the same manner as in Example 1 was added to this alkaline mixed solution, and the mixture was aged at 55° C. for 4 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 7.2.
[0097] The hydrotalcite particles obtained in the previous step were molded into spherical beads having a diameter of 4 mm in the same manner as in Example 1, and a catalyst for the decomposition of ammonia was obtained in the same manner as in Example 1. The Ni / (Mg+Al+Ni) of the obtained catalyst was 0.154 (molar ratio).
[0098] <Example 3> MgSO 4 7H 2 O (727.4 g) and Al (SO 4 ) 3 8H 2 O (80.15 g) and NiSO 4 6H 2 2.25g of NaOH (63.25g) was dissolved in pure water to make 1500ml. 2 CO3 (14.82 g) was dissolved in 500 ml of the solution to prepare a total of 2000 ml of an alkaline mixed solution. The alkaline suspension obtained in the same manner as in Example 1 was added to this alkaline mixed solution, and the mixture was aged at 150° C. for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 13.8.
[0099] The hydrotalcite particles obtained in the previous step were molded in the same manner as in Example 1 to form spherical beads with a diameter of 4 mm. They were calcined in air at 800°C for 8 hours to obtain a porous oxide powder, which was then reduced in an air stream containing hydrogen and argon gas at 950°C for 4.0 hours to obtain an ammonia decomposition catalyst. The Ni / (Mg+Al+Ni) ratio of the catalyst obtained here was 0.074 (molar ratio).
[0100] <Example 4> MgSO 4 7H 2 O(33.1g) and Al(SO 4 ) 3 8H 2 O (120.2 g) and NiSO 4 6H 2 14 mol / L NaOH (671.0 ml) was dissolved in 14 mol / L NaOH (671.0 ml) and the total volume was 1500 ml. 2 CO 3 (14.82 g) was dissolved in 500 ml of the solution to prepare a total of 2000 ml of an alkaline mixed solution. The alkaline suspension obtained in the same manner as in Example 1 was added to this alkaline mixed solution, and the mixture was aged at 150° C. for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 13.8.
[0101] The hydrotalcite particles obtained here were molded into spherical beads with a diameter of 4 mm in the same manner as in Example 1. They were calcined in air at 800°C for 8 hours to obtain a porous oxide powder, which was then reduced in an air stream containing hydrogen and argon gas at 1100°C for 4.0 hours to obtain an ammonia decomposition catalyst. The Ni / (Mg+Al+Ni) ratio of the catalyst obtained here was 0.16 (molar ratio).
[0102] <Example 5> MgSO 4 7H 2 O(33.1g) and Al(SO 4 ) 3 8H 2 O (120.2 g) and NiSO 4 6H 2 14 mol / L NaOH (671.0 ml) was dissolved in 14 mol / L NaOH (671.0 ml) and the total volume was 1500 ml. 2 CO 3 (14.82 g) was dissolved in 500 ml of the solution to prepare a total of 2000 ml of an alkaline mixed solution. The alkaline suspension obtained in the same manner as in Example 1 was added to this alkaline mixed solution, and the mixture was aged at 150° C. for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 13.8.
[0103] The hydrotalcite particles thus obtained were molded in the same manner as in Example 1 to form spherical beads having a diameter of 4 mm. The beads were calcined in air at 800° C. for 4 hours to obtain a porous oxide powder. Ru(NO ) having a Ru concentration of 10 g / L was added to 100 g of the obtained spherical bead catalyst for ammonia decomposition. 3 ) 3 The solution (20 mL) was dissolved in pure water to give 30 mL of solution, which was then sprayed onto the substrate and dried. After that, the substrate was reduced for 1.0 hour in an air stream containing hydrogen and argon gas at 800°C to obtain a catalyst for the decomposition of ammonia. The catalyst thus obtained had a Ni / (Mg+Al+Ni) ratio of 0.16 (molar ratio), and the average particle sizes of the metallic Ni particles and metallic Ru particles were each 12 nm. The supported metal (Ru) content was 0.2 wt%.
[0104] <Example 6> MgSO 4 7H 2 O(33.1g) and Al(SO 4 ) 3 8H 2 O (120.2 g) and NiSO 4 6H 2 14 mol / L NaOH (671.0 ml) was dissolved in 14 mol / L NaOH (671.0 ml) and the total volume was 1500 ml. 2 CO3 (14.82 g) was dissolved in 500 ml of the solution to prepare a total of 2000 ml of an alkaline mixed solution. The alkaline suspension obtained in the same manner as in Example 1 was added to this alkaline mixed solution, and the mixture was aged at 150° C. for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 13.8.
[0105] The hydrotalcite particles thus obtained were molded in the same manner as in Example 1 to form spherical beads having a diameter of 4 mm. These were then calcined in air at 800° C. for 4 hours to obtain a spherical ammonia decomposition catalyst. 2 (Pt(CN) 4 )·3H 2 A 30 ml solution of O (0.42 g) dissolved in pure water was sprayed onto the substrate, dried, and then reduced for 1.0 hour in an air stream containing hydrogen and argon gas at 800°C to obtain a catalyst for ammonia decomposition. The catalyst thus obtained had a Ni / (Mg+Al+Ni) ratio of 0.16 (molar ratio), and the average particle sizes of the metallic Ni particles and metallic Pt particles were each 11 nm. The supported metal (Pt) content was 0.2 wt%.
[0106] <Comparative Example 1> 1080.0 g of magnesium oxide powder and 110.3 g of α-alumina powder were mixed to form 4 mm spherical beads. These were then calcined at 1000°C for 4 hours in air to obtain spherical ammonia decomposition catalysts. 3 ) 2 6H 2 A 100 ml solution of O (21.84 g) dissolved in pure water was sprayed onto the substrate, dried at 85°C for 24 hours, and then reduced at 800°C for 1.0 hour in an air stream containing hydrogen and argon gas to obtain an ammonia decomposition catalyst. The Ni / (Mg+Al+Ni) ratio of the catalyst obtained here was 0.03 (molar ratio).
[0107] <Comparative Example 2> The α-alumina powder was formed into 3 mm spherical beads. They were then calcined at 1000°C for 4 hours in air. 100 g of the obtained spherical beads were mixed with Ni(NO 3 )2 6H 2 A 100 ml solution of O (58.50 g) dissolved in pure water was sprayed onto the substrate, dried, and then reduced at 800°C for 1.0 hour in an air stream containing hydrogen and argon gas to obtain an ammonia decomposition catalyst. The Ni / (Al+Ni) ratio of the catalyst obtained was 0.074 (molar ratio).
[0108] <Comparative Example 3> MgSO 4 7H 2 O(100.21g) and Al(SO 4 ) 3 8H 2 O (180.3 g) and NiSO 4 6H 2 2.33g of NaOH was dissolved in pure water to make 1500ml. 2 CO 3 (14.82 g) was dissolved in 500 ml of the solution to prepare a total of 2000 ml of an alkaline mixed solution. The mixed solution of magnesium salt and aluminum salt was added to this alkaline mixed solution, and the mixture was aged at 150° C. for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 10.8.
[0109] The hydrotalcite particles thus obtained were molded in the same manner as in Example 1 to form spherical beads having a diameter of 4 mm. The beads were then calcined in air at 800° C. for 4 hours to obtain a porous oxide powder. RuCl 3 (1.02g) was dissolved in pure water and 30ml of the solution was sprayed onto the substrate, dried, and then reduced for 1.0 hour in an air stream containing hydrogen and argon gas at 800℃ to obtain a catalyst for ammonia decomposition. The catalyst obtained had a Ni / (Mg+Al+Ni) ratio of 0.006 (molar ratio), and the average particle sizes of the metallic Ni particles and metallic Ru particles were each 10nm. The supported metal (Ru) content was 0.2wt%.
[0110] <Comparative Example 4> Al(SO 4 ) 3 8H2 O (88.20 g) and NiSO 4 6H 2 380.55 g of NaOH was dissolved in pure water to make 1500 ml. 2 CO 3 (14.82 g) was dissolved in 500 ml of the solution to prepare a total of 2000 ml of the alkaline mixed solution. 4 7H 2 O (261.99g) and Al 2 (SO 4 ) 3 8H 2 1000 ml of an aqueous solution of O (86.16 g) was added, and the mixture was aged at 150° C. for 12 hours to obtain hydrotalcite particles. The pH of the reaction solution at this time was 11.1.
[0111] The hydrotalcite powder thus obtained was molded into spherical beads having a diameter of 4 mm in the same manner as in Example 1. The powder was calcined in air at 800°C for 2 hours to obtain a porous oxide powder, which was then reduced in an air stream containing hydrogen and argon gas at 800°C for 1.0 hour to obtain an ammonia decomposition catalyst. The Ni / (Mg+Al+Ni) ratio of the catalyst thus obtained was 0.574 (molar ratio).
[0112] [Table 1]
[0113] [Table 2]
[0114] In the catalyst for decomposing ammonia according to the present invention, only nickel components are precipitated as metallic nickel particles from an oxide containing magnesium, aluminum and nickel with a spinel structure, and nickel metal is contained on the surface and / or pore surface of the oxide containing magnesium and aluminum. The catalyst for decomposing ammonia according to the present invention can decompose ammonia into hydrogen and nitrogen with high efficiency even if the nickel content of the active metal species is as small as 1 to 30 wt%. Furthermore, the catalyst starts to show catalytic activity for ammonia decomposition at a reaction temperature of about 300°C, and shows sufficient ammonia decomposition properties with an ammonia gas decomposition rate of about 80% or more at 600°C. In addition, the catalyst according to the present invention has high crushing strength, and shows the same ammonia decomposition properties as when it was used for the first time, even after 10 repeated uses. [Industrial Applicability]
[0115] This invention relates to the decomposition of ammonia, and by using this invention, a mixed reformed gas containing nitrogen and hydrogen can be efficiently obtained from ammonia. The present invention can be widely applied to hydrogen production technology, and will make a great contribution to the environmental field, where ammonia is treated to make it odorless, and the energy field, where ammonia is decomposed into nitrogen and hydrogen to obtain hydrogen.
Claims
1. 1. A catalyst for the decomposition of ammonia, comprising at least magnesium, aluminum and nickel, wherein the magnesium and aluminum are in the form of a composite oxide, the nickel is in the form of metallic nickel, and comprising 10 to 50 wt % magnesium, 5 to 35 wt % aluminum and 1 to 30 wt % nickel.
2. 2. The catalyst for decomposing ammonia according to claim 1, wherein the average particle size of the metallic nickel in the catalyst is 1 to 50 nm.
3. 2. The catalyst for decomposing ammonia according to claim 1, wherein the BET specific surface area of the catalyst is 5 to 100 m 2 / g of an ammonia decomposition catalyst.
4. 2. The catalyst for decomposing ammonia according to claim 1, comprising one or more metals selected from the group consisting of gold, silver, platinum, palladium, ruthenium, cobalt, iron, rhodium, iridium, rhenium, copper, manganese, chromium, vanadium, and titanium, each having an average particle size of 50 nm or less.
5. 2. The catalyst for decomposing ammonia according to claim 1, wherein the average crushing strength of the catalyst is 3 kgf / cm 2 The above is an ammonia decomposition catalyst.
6. A method for decomposing ammonia, comprising the step of: decomposing ammonia using the catalyst for decomposing ammonia according to claim 1.
7. A method for producing a mixed reformed gas containing hydrogen and nitrogen by reacting ammonia in the presence of the ammonia decomposition catalyst according to claim 1.
8. 2. The method for producing a catalyst for decomposing ammonia according to claim 1, wherein hydrotalcite particles containing constituent elements are produced as a precursor by a coprecipitation reaction, a molded body is produced, heated and sintered to form a porous catalyst body, and then heated and reduced.
Citation Information
Patent Citations
Catalyst for decomposing ammonia and method for producing the catalyst, and method for producing hydrogen using the catalyst
JP2011224555A